PELATIHAN TATA RIAS PENGANTIN DALAM UPAYA MENUMBUHKAN KEMANDIRIAN WARGA BELAJAR PAKET C DI PKBM NURUL ISLAM - Utami, Sri Dian; Meilya, Ika Rizqi; Muis, Abdul (Comm-Edu (Community Education Journal), 2025)
This research article aims to find out bridal makeup training in an effort to foster the independence of package C learning citizens at PKBM nurul islam karawang. the background of this training is the high dropout rate, especially for women so that this training exists. The importance of the research topic is the relevance of learning needs to learning citizens, bridal makeup has high economic value and practical skills so that it can foster economic independence. This research uses a qualitative descriptive method. This data collection technique uses observation and semi-structured interviews with research subjects totaling 5 people including 1 manager, 1 instructor, and 3 learning citizens. Data collection using interview, observation, and documentation methods. The conclusion of this research is that all bridal makeup training processes carried out at PKBM are well implemented and in accordance with existing mechanisms. In the process of implementing this training using the Learning by doing method. The instructor will explain the material and also provide teaching materials in the form of modules and practice with the media props or models, then the participants will practice following the instructor to the model. The results of this training have an impact on the independence of the trainees where they are very happy to have new skills so that in the future they can open jobs and entrepreneurship independently.